(untitled) (Ustozlar uchun, 2025)
Annotation: This article analyzes the influence of social media platforms on the modern use of the English language. It explores how online communication, digital culture, and social networking have changed the structure, vocabulary, and style of English. The study emphasizes that while social media promotes creativity and global communication, it also raises concerns about grammar simplification, slang overuse, and the decline of formal writing. The findings show that social media has become a powerful force shaping the evolution of modern English, reflecting the dynamic interaction between language and technology.